Safeguarding Wild Plant Genetic Resources of Georgia within the Millennium Seed Bank Partnership - Mikatadze-Panstulaia, Tsira; Kolbaia, Sandro; Gogoladze, Ana (European Journal of Sustainable Development, 2019)
Working group of the Department of Plant Conservation of the National Botanical Garden of Georgia (NBGG) have been participating in the global Millennium Seed Bank Partnership, led by the Royal Botanic Gardens, Kew since 2005. During the 2005-2018 period, within the scope of MSB-1 and MSB-2, seeds and herbarium samples of more than 1750 plant species and interspecific taxa, belonging to 107 families and 483 genera (more than 41% of Georgia’s flora) – 348 endemics of Caucasus and 151 endemics of Georgia, have been secured in the National Seed Bank of Georgia (NSB). Seed Bank data are managed in BRAHMS (Department of Plant Sciences of Oxford University). The collection of wild plant species is accompanied by the comprehensive database of geographical, botanical and habitat information. Later phase involves laboratory treatment and germination/viability testing (at least 500 seeds per species) and the long-term deposition and storage (under -20?C temperature) at the National Seed Bank of Georgia. The duplicates of seed collection and herbarium vouchers are stored at the Millennium Seed Bank of Royal Botanic Gardens, Kew, UK. Germination capacity and viability of collections in NSB is determined before cold storage of seeds, while at the MSB already banked seeds are tested. Keywords: Seed bank; Ex-situ conservation; Plant diversity; Botanical garden; Genetic resources